2016
DOI: 10.1063/1.4958837
|View full text |Cite
|
Sign up to set email alerts
|

Improved interfacial and electrical properties of Ge MOS capacitor by using TaON/LaON dual passivation interlayer

Abstract: The effects of TaON/LaON dual passivation interlayer on the interfacial and electrical properties of Ge metal-oxide-semiconductor (MOS) capacitor with HfO 2 gate dielectric are investigated. As compared to its counterpart with only LaON as passivation interlayer, the formation of HfGeO x and LaHfO x , which would degrade the interfacial quality, is effectively suppressed due to the strong blocking role of the TaON barrier layer against Hf diffusion. As a result, excellent interfacial and electrical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…So the stack with dual IPL, which has an IPL (such as LaON) to form superior interface with Ge and covered by another IPL (such as YON) to suppress the diffusion of Ge and high‐ k dielectric above, is a good proposal to further improve the interface quality. Based on this, another dual IPL of TaON/LaON has also been proposed and further investigated .…”
Section: Resultsmentioning
confidence: 99%
“…So the stack with dual IPL, which has an IPL (such as LaON) to form superior interface with Ge and covered by another IPL (such as YON) to suppress the diffusion of Ge and high‐ k dielectric above, is a good proposal to further improve the interface quality. Based on this, another dual IPL of TaON/LaON has also been proposed and further investigated .…”
Section: Resultsmentioning
confidence: 99%
“…4 to further illustrate their interface quality. Obviously, as Ta content increases until 31.4%, the peak area of GeO 𝑥 is decreased and then a turnaround is observed for excessive Ta incorporation (42.7%), which indicates that incorporation of a few Ta can suppress the formation of the unstable GeO 𝑥 due to its effective blocking role against diffusion of O, [10] and when excessive Ta is incorporated, the interface quality is degraded because of the increased Ge diffusion from the substrate into the interlayer as shown by the Ge 3𝑑 peak in Fig. 4(d) to enhance the growth of GeO 𝑥 .…”
Section: Binding Energy (Ev)mentioning
confidence: 99%
“…[8] For solving the problem, Ji et al [9] prepared a LaTaON dielectric used as a passivation interlayer by doping Ta into La-based oxides in N 2 atmosphere, achieving a good interfacial quality and electrical characteristics. Further, Cheng et al [10] reported that incorporation of Ta into LaON can improve its hygroscopic nature, and directly used LaTaON as the high-𝑘 gate dielectric of Ge MOS and obtained good results. [11] As a deep study, in this work, the effects of the Ta content in the LaTaON gate dielectric on interfacial and electrical properties of Ge MOS capacitors are further investigated to achieve more excellent high-𝑘 LaTaON gate dielectric by optimizing the Ta content.…”
mentioning
confidence: 99%
“…Obvious improvements after nitrogen incorporation were obtained and LaON achieved a low D it with the Ge substrate (4.96 × 10 11 cm −2 •ev −1 ). Moreover, La-based ternary oxides and dual passivation layers have been investigated with good results available, and the characteristics of Ge MOS devices with La-based dielectrics and/or passivation layers reported recently are summarized in Table 5 [56,[127][128][129][130][131][132]. The ZrO 2 /La 2 O 3 dielectric stack has been applied by W. B. Chen et al in Ge n-MOSFET with a laser annealing (LA) treatment to increase its gate capacitance density [133].…”
Section: Ge and Iii-v Metal-oxide-semiconductor (Mos) Devicesmentioning
confidence: 99%